2012
DOI: 10.1186/1471-2164-13-47
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Profiling provides a robust framework for physical mapping and sequencing in the highly complex and repetitive wheat genome

Abstract: BackgroundSequencing projects using a clone-by-clone approach require the availability of a robust physical map. The SNaPshot technology, based on pair-wise comparisons of restriction fragments sizes, has been used recently to build the first physical map of a wheat chromosome and to complete the maize physical map. However, restriction fragments sizes shared randomly between two non-overlapping BACs often lead to chimerical contigs and mis-assembled BACs in such large and repetitive genomes. Whole Genome Prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…KeyGene (www.keygene.com) recently developed a new approach called Whole Genome Profiling (WGP, van Oeveren et al 2011) that is based on the sequencing of the ends of restriction endonuclease fragments after digestion of BAC pools. The application of WGP to a subset of the wheat chromosome 3B physical map (Philippe et al 2012) demonstrated that this is a viable approach for a complex genome such as wheat and that it reduces the amount of chimeric and misassembled clones compared to the SNAPshot method while providing sequence tag information that can be used to support pooling strategies for sequencing. Thus, robust methodologies and protocols are now in place for assembling reliable physical maps in the Triticeae genomes.…”
Section: Establishment Of Genome Resources For Physical Mapping In Thmentioning
confidence: 99%
“…KeyGene (www.keygene.com) recently developed a new approach called Whole Genome Profiling (WGP, van Oeveren et al 2011) that is based on the sequencing of the ends of restriction endonuclease fragments after digestion of BAC pools. The application of WGP to a subset of the wheat chromosome 3B physical map (Philippe et al 2012) demonstrated that this is a viable approach for a complex genome such as wheat and that it reduces the amount of chimeric and misassembled clones compared to the SNAPshot method while providing sequence tag information that can be used to support pooling strategies for sequencing. Thus, robust methodologies and protocols are now in place for assembling reliable physical maps in the Triticeae genomes.…”
Section: Establishment Of Genome Resources For Physical Mapping In Thmentioning
confidence: 99%
“…Substantial progress has been made in identifying more than 80% of the genes in the large genomes of Triticeae crops such as barley (Mayer et al, 2011) and wheat (Philippe et al, 2012). These resources allow us to investigate genome dynamics by using phylogenomics and comparative genomics analysis tools to facilitate the identification of key genes such as MONOPTEROS, ABI3, FUS3, LEC2, AFL B3 etc.…”
Section: Seed Biologymentioning
confidence: 99%
“…Whole Genome Profi ling (WGP TM ) is an alternative method for the establishment of the chromosome physical maps developed based on a next-generation sequencingbased technology (van Oeveren et al 2011 ). The effi ciency of WGP on physical mappings of wheat chromosomes has been demonstrated by comparison with that of SNaPshot (Philippe et al 2012 ).…”
Section: Bac Contig Constructionmentioning
confidence: 99%
“…After fi ltering BACs, assembly of the fi ngerprints representing nine and ten times equivalent of 6BS and 6BL, respectively, was performed with the FingerPrinted Contigs (FPC) software (Soderlund et al 1997 ). A stepwise method was used for the assembly to further improve the quality of BAC contigs, which was defi ned by Paux et al ( 2008 ) during the construction of chromosome 3B physical map and fi nally modifi ed by Philippe et al ( 2012 ). The physical maps of chromosome 6B have been successfully established to have an estimated chromosomal coverage of more than 90 %.…”
Section: Bac Contig Constructionmentioning
confidence: 99%